2014
DOI: 10.1177/0961203314536245
|View full text |Cite
|
Sign up to set email alerts
|

Antibody against chromatin assembly factor-1 is a novel autoantibody specifically recognized in systemic lupus erythematosus

Abstract: Autoantibodies to proliferating cell nuclear antigen (PCNA) are specifically, if rarely, present in systemic lupus erythematosus (SLE) patient sera. Even SLE patients lacking PCNA reactivity often show reaction to PCNA-binding protein. Here, immunoreactivity to chromatin assembly factor-1 (CAF-1), an essential molecule for DNA replication and a PCNA-binding protein, was compared for the sera of SLE patients, normal healthy controls (NHCs) and other disease controls, and in autoimmune sera reactive to standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We evaluated these 33 publications in detail. We found that 23 publications fulfilled the eligibility criteria (3006 patients; Figure 1) [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. While all studies investigated SLE patients, only 6 of them focused on LN [13,19,22,25,27,31].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We evaluated these 33 publications in detail. We found that 23 publications fulfilled the eligibility criteria (3006 patients; Figure 1) [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. While all studies investigated SLE patients, only 6 of them focused on LN [13,19,22,25,27,31].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies were conducted in Asia (11 studies), while others were from Europe, northern America, and Africa (eight, two, and two studies, respectively). There were 15 cross-sectional studies [14,17,19,21,22,23,24,26,27,29,31,32,33,34,35] and eight prospective cohort studies [13,15,16,18,20,25,28,30]. All studies were conducted in adults except for one study which was done in children with juvenile-onset SLE [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations